Perancangan industri skala menengah minyak tamanu dan produk sampingnya - Ika Amalia Kartika; Adil Akbar Muhammad; Rofiq Yanu Faisya; Fachrezky Novalsyah (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
Tamanu oil is rich in active compounds beyond just fatty acids, including calophyllolide, inophyllums, calanolides, tamanolides, and coumarins, all of which offer antioxidant, anti-aging, anti-inflammatory, anti-UV, and anti-bacterial benefits. This makes tamanu oil a promising ingredient for skincare products such as facial oils, soaps, and shampoos. The oil can be produced by mechanical and/or solvent extraction. This research aimed to develop a medium-scale tamanu oil industry and its by-products from Calophyllum fruits, identify suitable production technologies, design a business model using the business model canvas, and conduct a feasibility analysis. The feasibility analysis was carried out by taking into account technical and technological, market and marketing, environmental, management and organizational, and financial aspects. The financial aspect included determining the B/C ratio, payback period, net present value, and return of investment. The production process tested in this study utilized fresh Calophyllum seeds and employed hot screw pressing along with binary solvents for extraction. The outputs from processing 1000 kg of calophyllum fruits included 141 kg of virgin tamanu oil, 57 kg of tamanu oil, 7.05 kg of resin, 594 kg of biopellets, and 142.2 kg of animal feed. The feasibility study indicated a positive net present value, a B/C ratio of 1.53, a payback period of 1.04 years, and a return on investment of 95.31%, confirming that establishing and operating a tamanu oil industry and its byproducts from calophyllum fruits is viable.